A diagnostic cohort study on the accuracy of 18-fluorodeoxyglucose (18FDG) positron emission tomography (PET)-CT for evaluation of malignancy in anterior mediastinal lesions: the DECiMaL study. Issue 2 (6th February 2018) - Proli, Chiara; De Sousa, Paulo; Jordan, Simon; Anikin, Vladimir; Devaraj, Anand; Love, Susannah M; Shackcloth, Michael; Kostoulas, Nikolaos; Papagiannopoulos, Kostas; Haqzad, Yama; Loubani, Mahmoud; Sellitri, Francesco; et al.
Abstract : Objectives: The aim of this study is to collate multi-institutional data to determine the value by defining the diagnostic performance of fluorodeoxyglucose positron emission tomography (FDG PET)/CT for malignancy in patients undergoing surgery with an anterior mediastinal mass in order to ascertain the clinical utility of PET/CT to differentiate malignant from benign aetiologies in patients presenting with an anterior mediastinal mass Setting: DECiMaL Study is a multicentre, retrospective, collaborative cohort study in seven UK surgical sites. Participants: Between January 2002 and June 2015, a total of 134 patients were submitted with a mean age (SD) of 55 years (16) of which 69 (51%) were men. We included all patients undergoing surgery who presented with an anterior mediastinal mass and underwent PET/CT. PET/CT was considered positive for any reported avidity as stated in the official report and the reference was the resected specimen reported by histopathology using WHO criteria. Primary and secondary outcome measures: Sensitivity, specificity, positive and negative predicted values of [18F]-FDG PET in determining malignant aetiology for an anterior mediastinal mass. Results: The sensitivity and specificity of PET/CT to correctly classify malignant disease were 83% (95% CI 74 to 89) and 58% (95% CI 37 to 78). The positive and negative predictive values were 90% (95% CI 83% to 95%) and 42% (95% CI 26% to 61%). Conclusions: The results of our study suggest reasonable sensitivity but no specificity implying that a negative PET/CT is useful to rule out the diagnosis of malignant disease whereas a positive result has no value in the discrimination between malignant and benign diseases of the anterior mediastinum.